Biología reproductiva de Hypophthalmus edentatus “maparate” (Agassiz, 1829) y Brycon amazonicus (Spix & Agassiz, 1829) "sábalo cola roja" en la cuenca media del río Putumayo, Loreto - Perú - Sotelo Lescano, Luis Olabo (2022)
An investigation was carried out from November 2020 to October 2021, to know the reproductive biology of Hypophthalmus edentatus (Agassiz, 1829) "maparate" and Brycon amazonicus (Spix & Agassiz, 1829) "sábalo cola roja", in the middle basin of the Putumayo River, Loreto – Peru. The objective of the study was to estimate the size at first sexual maturity, determine the sexual proportion and calculate the gonadosomatic index of the species. The methodology described by Tresierra, A., & Culquichicón, Z., was used. The specimens were obtained from the fishing landing port, the Municipal Market of the city of San Antonio de El Estrecho and through exploratory fishing. For H. edentatus, the size at sexual maturity was estimated at 28.3 cm standard length for females and 26.5 cm for males. A total of 192 individuals they registered for H. edentatus, 127 (66%) females and 65 (34%) males. The gonadosomatic index (IGS) in females presented its highest value in April, with a value of 1.6%, and its lowest value (0.14%) in January. The maximum value in males was obtained in April, with 0.6%, and its minimum value in March, with 0.05%. For B. amazonicus, the size at first sexual maturity registered a standard length of 25.1 cm for females and 24.8 cm for males. 152 individuals were recorded, of which 101 (66%) were females and 51 (34%) males. The gonadosomatic index (IGS) in females presented its highest value in January, with a value of 6.99%, and its lowest value (0.17%) in July. In relation to males, the maximum value was obtained in January, with 1.09%, and its minimum values in July and October, with 0.2%. It is concluded that the males of Hypophthalmus edentatus and Brycon amazonicus mature in less time than the females.